Competitive and/or Cooperative Interactions of Listeria monocytogenes With Bacillus cereus in Dual-Species Biofilm Formation - Alonso, Vanessa Pereira Perez; Harada, Andréia Miho Morishita; Kabuki, Dirce Yorika (Frontiers in Microbiology, 2020)
Microorganisms in dairy industries can form mono-species, dual-species or multi-species biofilms, showing cooperative or competitive behaviors, which might contribute to the reduction of efficiency of cleaning and sanitization processes and eventually turn into a potential source of contamination. This study proposes to evaluate the behavior of Listeria monocytogenes in mono-species biofilms and co-cultured with Bacillus cereus. The isolates were from dairy origins and the selection occurred after studies of competition among species. The biofilm formations on AISI 304 stainless steel at 25° C in stationary culture were analyzed to observe the cooperative or competitive interactions among species as well as the effect of pre-adhered cells. Biofilm formation assays were performed in four experiments: Experiment 1: in the presence of strains of antagonistic substance producer B. cereus (+); Experiment 2: extract of the antagonistic substance of B. cereus; Experiment 3: pre-adhered cells of B. cereus and Experiment 4: pre-adhered cells of L. monocytogenes. Subsequently, cooperative behavior was observed by scanning electron microscopy (SEM). The L. monocytogenes mono-species biofilms counts of above 5 log CFU/cm² was also observed in dual-species biofilms in the presence of B. cereus (non-producers of antagonist substance) showing cooperative behavior between species. However, in the presence of antagonistic substance produced by B. cereus the counts were lower 1.39 and 1.70 log CFU/cm² (p > 0.05), indicating that the antagonistic substance contributes to competitive interactions. These data are relevant for the development of new studies to control L. monocytogenes in the dairy industry.